STUDY OF ANTHROPOMORPHIC FIGURINES OF THE NORTH-EASTERN CAUCASUS - Davudov, O M (History, Archeology and Ethnography of the Caucasus, 2015)
The article presents information on the anthropomorphic figurines found in the North-East Caucasus, provides the review of the available literature on the problems associated with small plastic arts of Dagestan and Mountainous Chechnya. The author of the article analyzes the gradual process of formation of scientifically verified concepts of male and female cast bronze figurines, their classification, chronology and semantics, starting from the first articles about the mysterious images. The article covers debate on anthropomorphic plastic arts of Dagestan. The problem of chronology is particularly disputable.The difficulty of dating the finds from the places of worship is due to the peculiarities of the sites, where the treasure has been accumulated for a long time. Thus, the objects belonging to different epochs may occur here. After extensive study the researchers of Dagestan have arrived at a common view that volume figurines mainly date back to the 7th–8th centuries with a possible extension of the dating to the 1st–10th centuries, considering the Bezhta-Dai archaeological culture they are associated with, and chronologically precede flat and plano-concave figurines.
Keywords: anthropomorphic images of the North-East Caucasus; review of literature on small plastic arts; images of deities and deified characters; West Dagestan and Mountainous Chechnya.